USING TWO STAY-TWO STRAY (TSTS) TO IMPROVE SPEAKING ACHIEVEMENT OF THE TENTH GRADESTUDENTS OF SMAN 10 PALEMBANG - Eza Septy Lesia; Nike Angraini (Universitas Indo Global Mandiri, 2018)
This research was conducted to improve speaking achievement of the tenth grade students of SMA N 10 Palembang in academic year of 2017/2018 by using Two Stay Two Stray (TSTS) method.The objective of this research was to improve the speaking ability. The method of this research was quasi experimental design. There were 20 students taken as the sample for both experimental and control group, respectively. The speaking test, in pretest and posttest, was used to collect the data. The data of speaking test was then analyzed by using SPSS program. The research findings revealed that holistically there a significant improvement on the students’ speaking achievement who were taught by using TSTS Method. Analytically, there a significant improvement on the students’ speaking aspects achievement who were taught by using TSTS Method where the highest score of speaking aspects in the experimental group were in fluency (0.85) and pronunciation (0.75). Also, there was a significant mean difference between the students’ speaking achievement who were taught by TSTS method and those who were not.Key words: Two Stay Two Stray, speaking achievement